Entrelaçando pontos – de fora para dentro, de dentro para fora: ação e formação da terapia ocupacional social na escola pública - Pan, Lívia Celegati (2019)
Occupational therapy has produced knowledge and practices about/in schools from different perspectives, one of them focuses on the demands arising from the social issue, pioneered in the Brazilian scenario by METUIA/UFSCar. The group brings together researchers, professors, professionals and graduate and undergraduate students and has been dedicating, since its inception, to teaching and research in social occupational therapy, involving occupational-therapeutic interventions aimed at populations in social vulnerability, particularly young people from urban popular groups, through university extension. The work presented here sought to understand what was produced by METUIA/UFSCar in its teaching, research and extension proposals in the public schools, in relation with this institution and about it and, equally, what results can be inferred from these actions, covering a period that begins in 1998 and runs until 2017. For the accomplishment of the study, besides the composition of the theoretical referential for the analysis in the scope of the Basic Education and the social occupational therapy in Brazil, it was held a survey of bibliographic productions concerning the school, of extension projects developed by the group in public schools and in relation with it, of the professionals who acted as occupational therapists in these projects and of students who have gone through professional internships in METUIA/UFSCar. The set of results was composed by: - 45 bibliographic productions: three research reports, two doctoral theses, six master's dissertations, nine scientific initiation reports, eight book chapters and 17 texts in journals, including research articles, experience reports and essays; - final reports of 16 extension projects; - interviews with 10 occupational therapists who worked for METUIA/UFSCar in the public school; - 42 questionnaires answered by former undergraduate students who went through a professional internship with METUIA/UFSCar and interviews with seven of these ex-students. The analysis of the results allows considerations in the sense of a proposition of action and formation of social occupational therapy in the public school that is in line with a proposal of radical Inclusive Education that intertwining actions that deal with the care of poor adolescents and young people and theirs possible supportive social networks, is done “from the outside in, from the inside out”. This methodology involves the use of social technologies of social occupational therapy: Activity Workshops, Dynamics and Projects, Individual and Territorial Follow-up; Articulation of Resources in the Social Field; and Dynamization of the Social Care Network, as well as four dimensions that permeate them: Handling Conflict, Sensitivity for Working with Adolescents and Youth, Project Management and Care Production. It is concluded that this set of productions points out important demands to be worked by occupational therapists in their practices, beyond those already traditionally placed in the scope of disabilities and global developmental disorders, problematizing its contribution to the Basic Education in Brazil that persists with marked social inequality in the XXI century.